Necessity and proportionality in international peace and security law - (Lawyer) (The Lieber studies, 2021)
Necessity and proportionality occupy a firm place in the international law governing the use of force by states. Perhaps most importantly for practical purposes, the exercise of the right of self-defense, as recognized in Article 51 of the United Nations Charter, is subject to the requirements of necessity and proportionality, as the International Court of Justice determined in the Nicaragua case. Necessity and proportionality are also firmly anchored in the international law governing armed conflicts. In its Nuclear Weapons Advisory Opinion, the International Court of Justice even referred to one articulation of the idea of necessity, that directed against the causing of unnecessary suffering, as one of two "cardinal principles" of this body of law. However, beyond statement in such general terms, the realms of uncertainty and controversy soon begin. It is far from clear, for example, how to distinguish with precision between necessity and proportionality in the international law on self-defense and, in immediate connection herewith, what it means precisely to say that forcible action taken in the exercise of self-defense must be proportionate. It is all the less clear what legal significance, if any, necessity and proportionality possess in other contexts of the international law governing the use of force"--